Meningkatkan Motivasi Belajar Peserta Didik Sekolah Dasar Melalui Pemanfaatan Media LKPD Interaktif Berbasis Liveworksheet Pada Masa Revolusi Industri 4.0 - Joko Daryanto; Rukayah Rukayah; Sularmi Sularmi; Tri Budiharto; Idam Ragil Widianto Atmojo; Roy Ardiansyah; Dwi Yuniasih Saputri (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This service aims to increase the learning motivation of fourth grade elementary school students using interactive student worksheets based on live worksheets. The method used in this dedication is through training activities/workshops for teachers at SD Negeri Jajar, Surakarta and continued to be implemented for class IV students at SD N Jajar Surakarta totaling 15 students. The type of LKPD used in this service is interactive LKPD based on live worksheets. The results of this service indicate that the motivation of students has increased through the use of live worksheet-based interactive worksheets. The results of the first implementation were 2 or 13.3% of students in the good category, and 13 or 86.7% of students in the poor category. Then it increased in the second implementation which showed as many as 3 students or 20% in the very good motivation category, 9 students or 60% in the good category. This service activity provides insight for teachers to increase the optimal use of LKPD through an attractive platform, namely live worksheets.